Sorption and solubility of bioceramic endodontic sealers and sealer based on epoxy resin (Research, Society and Development, 2021)
Introduction: Endodontic cements are used in root canal filling and are associated with successful endodontic treatment, filling the spaces between the walls of the root canal and gutta-percha. The sorption and solubility of these materials are properties that are related to the process of remineralization of periapical tissues and antimicrobial capacity, in addition to being parameters linked to deleterious effects, such as cement degradation and the consequent recontamination of the root canal. Methods: AH Plus cements (Dentsply, São Paulo, SP, Brazil), MTA Fillapex (Angelus, Londrina, PR, Brazil) and Bio-C Sealer (Angelus, Londrina, PR, Brazil) were handled following the manufacturer's instructions and stored in an oven at 37°. Subsequently, they were weighed on a precision analytical balance so that the samples were then placed in distilled water for 24 hours in an oven at 37° and thus, after removing the excess, the samples underwent sorption and solubility tests, and the averages were compared by Tukey HSD test. Results: regarding sorption, it was observed that MTA Fillapex had the highest value, whereas the other cements had lower values and no statistically significant differences between them. AH-Plus cement had the lowest solubility value, while Bio–C cement had the highest. Conclusions: Even with values higher than those recommended by ISO standards, Bio-C and MTA-Fillapex cements are still suitable for clinical use.